2007
DOI: 10.5367/000000007781891504
|View full text |Cite
|
Sign up to set email alerts
|

Microfertilizing Sorghum and Pearl Millet in Mali

Abstract: Microfertilizing, consisting of applying small amounts of mineral fertilizer to the planting hole or pocket, was tested in Mali. Yields of sorghum increased by 34% and 52% compared with the control after applying 0.3 g of fertilizer per pocket for the years 2000 and 2001 respectively. For pearl millet, the corresponding yield increase was 48% and 67% for 2001 and 2003 respectively. Higher yield increases were observed when 6 g of fertilizer was applied per pocket than when 0.3 g of fertilizer was applied. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 6 publications
0
15
0
2
Order By: Relevance
“…Previous studies have shown that seed priming and micro-dosing can increase yield at a low cost [2][3][4][5]9,10,16]. Micro-dosing was also reported to improve the fertilizer use efficiency compared to broadcasting of fertilizer [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that seed priming and micro-dosing can increase yield at a low cost [2][3][4][5]9,10,16]. Micro-dosing was also reported to improve the fertilizer use efficiency compared to broadcasting of fertilizer [17].…”
Section: Discussionmentioning
confidence: 99%
“…Application of small amounts of mineral fertilizer in the planting hole is a more efficient way to apply mineral fertilizer compared to broadcasting. This method increases both yield and the efficiency of fertilizer application [2][3][4][5][6]. Another low-cost approach to increase yield under marginal dry land conditions is seed priming, a process of soaking seeds in water for a specific period prior to sowing [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Ce ratio permet d'identifier le meilleur traitement qui engendre un rendement additionnel et un gain monétaire optimal. Selon Aune et al (2007), il correspond au rapport entre la valeur totale de la production et le coût de la fertilisation. Pour Delville (1996) …”
Section: Détermination De La Rentabilité éConomiqueunclassified
“…Ces résultats sont en accord avec ceux obtenus précédemment, montrant que la microdose favorisait une augmentation du revenu des producteurs (Tabo et al, 2005(Tabo et al, , 2007Aune et al, 2007 ;Taonda et al, 2008) qui ont montré que la microdose favorisait une augmentation du revenu. Aune et al (2007) ont obtenu au Mali un RVC variant entre 9,33 et 9,37 pour le sorgho et 3,4 à 11,9 pour le mil avec des apports de 0,3 g/poquet du NPK (15-15-15) ou du DAP (18-46-0). Taonda et al (2008) ont montré que le revenu est multiplié par 2,5 lorsqu'on passe de dose vulgarisée à la microdose.…”
Section: Analyses Statistiquesunclassified
“…Micro-fertilization, consisting of applying small amounts of mineral fertilizer to the planting hole or pocket, could be a useful option for these areas. In Mali, a 50% yield increase was obtained for sorghum and pearl millet dry farming using the equivalent to just 3-8 kg fertilizer per hectare [79] (Table 2), instead of the usually recommended dosage being 10 or 20 times higher or more. Small quantities of fertilizer (0.3 g per seed) were applied simultaneously with seeds during sowing.…”
Section: Water Managementmentioning
confidence: 99%